Growth responses of strawberry (Fragaria × Ananassa Duch.) plants grown at different planting density using PVC pipe under protected cultivation (Bangladesh Journal of Botany, 2019)
Production of strawberry cv. Sweet Charlie under soilless system (Horizontal and A-shape structures) at six different planting densities using two diameters of PVC pipes in a actively ventilated poly house was attempted. Significant differences were observed in growth parameters, namely number of leaves, petiole length, plant height, plant spread and crown diameter. The results showed that the plants grown at D3 (20 plants/m2) significantly increased the number of leaves (9.76 and 12.49) and plant spread (24.44 and 25.69 cm) compared to other planting densities. The planting density significantly influenced the petiole length and plant height also in strawberry. The maximum petiole length (8.43 and 8.64 cm) and plant height (13.92 and 15.31 cm) were recorded from D3 (12 plants/m2), however non-significant difference was observed between D3 and D4. In future, these experimental results will prove very useful to find out most suitable plant geometry for better growth of strawberry.